Dampak Penggunaan Mulsa Plastik Hitam Perak Terhadap Pendapatan Usahatani Cabai Rawit Di Desa Pemenang Timur Kabupaten Lombok Utara - Azizah Ulfa; Bambang Dipokusumo; Muhammad Nursan (JURNAL AGRIMANSION, 2022)
Cayenne pepper is one of the vegetable commodities chosen by farmers in the District of Winner of North Lombok Regency. This is due to the climate and natural conditions in the District of Winner of North Lombok Regency which are suitable for the growth of chili pepper plants. (2) To study the income comparison of tanicabai rawit business in East Winning Village, North Lombok Regency. This study uses a descriptive method with the object of research is chili pepper farmers set as a purposive sampling area with the consideration that the research area is one of the places where farmers apply the use of silver black plastic mulch in the chili pepper business and the area that has the largest chili production of the four WinLombok Villages in Pe District. In this study, there were 16 respondents of cayenne pepper business that used silver black plastic mulch determined by the Census Method, while the respondents of chili pepper business that did not use mulch were determined by proportional random sampling, consisting of 4 Tunas Makbul Farmer Group, 6 Tunas Accept Farmer Group and 6 people. Based on the results of this study, the average production of cayenne pepper using black-silver plastic mulch is 1,996.75 Kg/LLG or 7,131.25 Kg/hectare, while the average production of chili peppers that do not use mulch is 1,320.56 Kg/LLG or 5,079.08 Kg/hectare 15,000 with an average selling price of Rp. 29,951,250.00 per LLG or IDR 106,968,750.00 per hectare, while the production value of chili peppers that do not use mulch is IDR 19,808,400.00 per LLG or IDR 76,186,200.00 per hectare, with an average production cost of chili using plastic mulch 14,681,726G or IDR 52,434,864, 28 per hectare, while the production cost of cayenne pepper that does not use mulch is Rp 9,457,971.54 per LLG or Rp 36,376,813.59 per hectare. Based on the results of research that has been carried out on the tanicabairawit business in East Pemenang Village, North Lombok Regency, then: (1). The average income earned by the cayenne pepper business that uses black-silver plastic mulch in Pemenang Timur Village, North Lombok Regency is IDR 15,269,488.00 per LLG or IDR 54,533,885.72 per hectare, while the average income of the chili pepper business that does not use mulch is IDR 10,350,428.46 per LLG per season or IDR 339,419. . (2). The business income of cayenne pepper that uses black-silver plastic mulch is Rp. 54,533,885.72 per hectare, which is higher than that which does not use mulch of Rp. 39,809,386.41 per hectare, so it can be said that the use of black-silver plastic mulch has an impact on business income of cayenne pepper.